Vocational and academic secondary educator's perceptions of career education in Class A-AAAA schools in Wyoming - Wagoner, Heather Teach, author; Daly, Joseph, advisor; Kees, Nathalie, committee member; Anderson, Sharon, committee member; Cook, Alicia Skinner, committee member (Colorado State University. Libraries, 2000)
The purpose of this study was to determine the perceptions of academic and vocational secondary educators on career education in Class A, AA, AAA, and AAAA schools in Wyoming. To achieve this objective, five research hypotheses were posed and five null hypotheses were tested. The independent variables were size of school (Class A-AAAA) and teacher type (Academic and Vocational). The dependent variables on the survey included: 1) Perception towards career education as measured by six constructs, 2) Use of Career education, 3) Method of Curriculum delivery, 4) Delivery of School to Work Systems, and 5) Technology and use of alternative technology for the delivery of career education. Two hundred and sixty-six returned surveys provided a 58% return rate: 51.5% of the respondents were vocational teachers and 48.5% were academic teachers. There were relatively equal proportions of respondents in each school size. Two-way analysis of variance procedure was used to test Ho1 and Ho5. Log Linear Analysis with cross tabulation and chi square test of significance was used to test Ho2-Ho4. Findings indicated differences related to teacher type. Academic teachers were less likely to support career education than vocational teachers. Vocational teachers viewed teachers as the key personnel in career education. Academic teachers viewed guidance counselors as the key personnel to assist with career education. Academic teachers perceived careers be delivered by a separate class; vocational teachers preferred infusion of career education. Vocational teachers had more competencies in using Alternative Technology when compared to academic teachers. It was clear that there were discrepancies in the use of Tech Prep and apprenticeships amongst large and small schools. A large percentage of small schools perceived career exploration opportunities as minimal. School to work programs and access to these initiatives is markedly less in small schools versus large schools. Implications suggest that integration of academic and vocational subjects and career education are a not uniformly delivered in the State of Wyoming. Qualitative analysis revealed that community was important; computer programs widely used and schools participated in on-site visits, job shadowing, and field trips.
Keywords: secondary education; academic guidance counseling; vocational education; school counseling